BNPs@Cur-Pd as a versatile and recyclable green nanocatalyst for Suzuki, Heck and Stille coupling reactions. Issue 1 (1st January 2020) - Jani, Muhammed Ali; Bahrami, Kiumars
Abstract: Herein, BNPs@Cur-Pd as a versatile and reusable nanocatalyst was successfully synthesized and used for C–C coupling reactions. The Suzuki, Heck and Stille coupling reactions with good to excellent yields were conducted with Pd. Also, the catalyst could be recycled and reused for several sequential runs without considerable Pd leaching or diminishing of reaction yields. This simple methodology can be based on green chemistry protocols by using the boehmite, Curcumin and PEG as support, ligand, and solvent, respectively.